Application of advanced phytoremediation techniques in soils and waters contaminated with heavy metals (Case study: Eshtehard Industrial Town) (Development Engineering Conferences Center Articles Database, 2026)
Heavy metal contamination in soil and water represents one of the most critical environmental challenges, with far-reaching consequences for human health and ecosystem sustainability. Due to the high concentration of polluting industries, the Eshtehard Industrial Town is recognized as a major hotspot for the release of such metals. This study was conducted with the overarching aim of improving environmental quality and enhancing the resilience of the industrial network in Eshtehard. The primary focus was placed on employing phytoremediation techniques to mitigate soil and water pollution, while simultaneously creating suitable green spaces to improve the working environment for industrial employees. The research adopted a descriptive–analytical approach. Data and imagery from the Google Earth Engine platform were utilized to identify areas contaminated with copper, zinc, and iron, and an analytical pollution map was generated. The findings revealed that certain sites exhibit higher levels of contamination and therefore require targeted management strategies. To integrate technical results with managerial insights, the SWOT framework was applied to identify strengths, weaknesses, opportunities, and threats associated with environmental management in the industrial town. Based on this analysis, practical strategies and plant-based recommendations were proposed, demonstrating that the use of selected species can provide a sustainable and cost-effective approach to reducing pollution and improving environmental quality in industrial areas.